The Venezuelan university curriculum. Epistemological and ontological analysis of teacher training. - Florez Villamizar, Isleyda (Universidad Francisco de Paula Santander, 2015)
The present study is a documentary review aimed at the establishment of a systematic analysis of the Venezuelan curriculum, for this purpose, the epistemological analysis of the university curriculum was initially assumed as a north, emphasizing it at a general level, to later locate it within the university and to close this analysis with the teacher training curriculum. Next, the analysis and interpretation of events of ontological order that characterize the teacher training curriculum is contemplated, for which the curricular development was assumed from the perspective of the Universidad Pedagógica Experimental Libertador, the current evidences of the curricular administration within this teacher training university were contemplated, to then refer to the process of curricular transformation that is currently taking place within this house of studies. The article closes with a series of final considerations generated from the interpretation of the previously mentioned elements.